Prevalência de helicobactérias e alterações na mucosa gástrica de cães saudáveis - Moutinho, Flavio Quaresma [UNESP]; Thomassian, A. [UNESP]; Watanabe, M.J. [UNESP]; Suzano, S.M.C. [UNESP]; Sequeira, J.L. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2007)
Prevalence, distribution and density of gastric helicobacter colonization were determined in 50 healthy dogs, characterizing the macroscopic and microcospic aspects of their mucosa. Helicobacter prevalence was 96%, with greater distribution in the gastric fundus and body. Although the presence of macroscopic alterations was high (58%), it was characterized as mild due to the predominance of less severe ones (65.5%). High prevalence of mostly monoclear cell infriltate (64.7%) was noted. Association between the presence of helicobacter and macro and microscopic alterations was not observed.
Prevalence of helicobacters and alterations in gastric mucosa of healthy dogs
Keywords: cão; Helicobacter; prevalência; dog; Helicobacter; prevalence